Sympathetic Neurons Regulate Cardiomyocyte Maturation in Culture - Kowalski, William J.; Garcia-Pak, Iris H.; Li, Wenling; Uosaki, Hideki; Tampakakis, Emmanouil; Zou, Jizhong; Lin, Yongshun; Patterson, Kira; Kwon, Chulan; Mukouyama, Yoh-Suke (Frontiers in Cell and Developmental Biology, 2022)
Embryos devoid of autonomic innervation suffer sudden cardiac death. However, whether autonomic neurons have a role in heart development is poorly understood. To investigate if sympathetic neurons impact cardiomyocyte maturation, we co-cultured phenotypically immature cardiomyocytes derived from human induced pluripotent stem cells with mouse sympathetic ganglion neurons. We found that (1) multiple cardiac structure and ion channel genes related to cardiomyocyte maturation were up-regulated when co-cultured with sympathetic neurons; (2) sarcomere organization and connexin-43 gap junctions increased; (3) calcium imaging showed greater transient amplitudes. However, sarcomere spacing, relaxation time, and level of sarcoplasmic reticulum calcium did not show matured phenotypes. We further found that addition of endothelial and epicardial support cells did not enhance maturation to a greater extent beyond sympathetic neurons, while administration of isoproterenol alone was insufficient to induce changes in gene expression. These results demonstrate that sympathetic neurons have a significant and complex role in regulating cardiomyocyte development.